PENGARUH KUALITAS PELAYANAN, HARGA DAN KEPUASAN TERHADAP LOYALITAS PENGGUNA JASA TRANSPORTASI PADA PO. BEJEU JEPARA (STUDI KASUS PADA PENGGUNA TRAVEL BEJEU JURUSAN SEMARANG – JEPARA) - Shena Adaby Amin; Ngatno Ngatno (Universitas Diponegoro, 2016)
This research motivated by the development of transportation business nowadays which harder because of the increasing of competitors. Transportation service company expect the high loyalty from the customer but in fact, the customer’s loyalty is still low. As well as happened to the kind of transportation service like Bejeu Jepara Semarang-Jepara route Travel.The aim of this study was to determine the effect of service quality, price and satisfaction toward transportation service customer’s loyalty of PO. Bejeu Jepara, Semarang-Jepara route. About 100 samples of respondents required and sample collection technique used was purposive sample. Data was analyzed using SPSS 20.0 which previously was conducted validity test, reliability, correlation coefficient, determination coefficient, simple and multiple regression analysis also Sobel test.The result showed that service quality and prices had an effect toward satisfaction so could influence the customer’s loyalty.The suggestion was PO Bejeu could improve the quality by repair the waiting room and depart according to the schedule so could arrive at the destination on time. Otherwise, in price determining, PO Bejeu was suggested to give discount or ticket price reduction on certain days so the low purchasing customer could use it.